2019
DOI: 10.1039/c8cy02306a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular water oxidation catalysis by zwitterionic carboxylate bridge-functionalized bis-NHC iridium complexes

Abstract: Carboxylate functionalized bis-NHC ligands allow for the stabilization of high-valent iridium intermediate species involved in homogeneous water oxidation catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…[22] In this regard, we have shown that the carboxylate group at the linker provides hemilabile properties to the ligand, allowing for the stabilization of catalytic intermediates through the k 3 -C,C',O-tridentate coordination mode. [23] However, in most complexes the bis-NHC ligand exhibits a k 2 -C,C bidentate coordination mode with an uncoordinated functional group in the skeleton that has shown to be a reactive site. [22] As a continuation of our studies on the catalytic applications of functionalized bis-NHC metal complexes, we have found that the zwitterionic complex, [Cp*IrCl{(MeIm) 2 CHCOO}] (1) (MeIm = 3-methylimidazol-2-yliden-1-yl), [22] which features a carboxylate bridge-functionalized bis-NHC ligand, efficiently catalyzes the reduction of CO 2 with hydrosilanes to selectively afford the corresponding silylformates.…”
Section: Introductionmentioning
confidence: 99%
“…[22] In this regard, we have shown that the carboxylate group at the linker provides hemilabile properties to the ligand, allowing for the stabilization of catalytic intermediates through the k 3 -C,C',O-tridentate coordination mode. [23] However, in most complexes the bis-NHC ligand exhibits a k 2 -C,C bidentate coordination mode with an uncoordinated functional group in the skeleton that has shown to be a reactive site. [22] As a continuation of our studies on the catalytic applications of functionalized bis-NHC metal complexes, we have found that the zwitterionic complex, [Cp*IrCl{(MeIm) 2 CHCOO}] (1) (MeIm = 3-methylimidazol-2-yliden-1-yl), [22] which features a carboxylate bridge-functionalized bis-NHC ligand, efficiently catalyzes the reduction of CO 2 with hydrosilanes to selectively afford the corresponding silylformates.…”
Section: Introductionmentioning
confidence: 99%
“…The operating frequency for 13 C{ 1 H} NMR was 150 MHz (on the 600 MHz instrument) or 201 MHz (on the 800 MHz instrument). All 1 H and 13 C{ 1 H} NMR spectra were referenced against residual 1 H resonances ( 1 H NMR) or 13 C{ 1 H} resonances ( 13 C{ 1 H} NMR) of the deuterated solvents. All spectra were recorded at 25 C unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…[6,9,10] There are a large number of homogeneous Ir precatalysts for catalytic water oxidation. Many leading efforts to study these molecular Ir catalysts have focused on the use of chemical oxidants (e.g., NaIO 4 and ceric ammonium nitrate), [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] with perhaps fewer studies on electrochemically driven water oxidation. [25][26][27][28][29] For example, Crabtree and coworkers identified the tris-aqua complex [Cp*Ir(H 2 O) 3 ] 2 (A) (Cp* ¼ pentamethylcyclopentadienyl) and the complex bearing the 2-(2-pyridyl)-2-propanolate ligand, B, as molecular water oxidation catalyst precursors at pH 7 and 1.7 V versus normal hydrogen electrode…”
Section: Introductionmentioning
confidence: 99%
“…Although IrO x nanoparticles are highly active for water oxidation catalysis, development of novel molecular WOCs could facilitate a better understanding of the mechanism and engender molecular design principles for future catalysts. We and others have studied a series of Cp*Ir­(III) (Cp* = pentamethyl­cyclopentadienyl, C 5 Me 5 – ) precatalysts, including one bearing the chelating pyalk ligand ( 1 in Chart , pyalk = (2-pyridyl)-2-propanolate). Upon chemical ,, or electrochemical activation, , 1 is oxidized to form a set of blue species that function as highly active and efficient WOCs.…”
Section: Introductionmentioning
confidence: 99%